DAYA PREDIKSI PAJAK, LABA DAN ARUS KAS TERHADAP PAJAK MASA DEPAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ardi Hamzah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
The objectives of this research are to examine prediction power of tax, earnings, and cash flow on future tax with firms size namely asset total and sales value as control variable. The samples of data are manufactur firm that listed in Indonesia Stock Exchange in period 2003 – 2008. Data total is 270 firm that fulfill requirement namely have not negative tax, earnings, and cash flow. The source of data is Indonesian Stock Exchange. Technic of data gathered is purposive sampling. Independent variables are taxt-1, earningst-1 and cash flowt-1, while control variables are firm size namely asset total dan sales value. Dependent variable is taxt. The analysis that use in this research is statistic descriptif and regression test. The result of this research indicate that partially earnings, cash flow, and firm size namely asset total and sales value have significantly effect on tax future, while tax have not significantly effect on future tax. For examining simultantly indicate that tax, earnings, cash flow, and firm size have significantly effect on future tax. The prediction power earnings on future tax better than cash flow and tax.